(untitled) (Fiep Bulletin - online, 2014)
The Physical Education, while area of knowledge in the school must systemize learning and education situations that guarantee to the pupils the appropriation of the understanding on knowledge that, for the pupils, is practical, atitudinais, factual and conceptual. Thus we detach the lateral domain as one of the specific contents of disciplines of Physical Education, and presents the hypotheses that they search to explain this domain. Currently, what we have observed in the lessons of this disciplines is that the pupils identify the dominant side during the carried through activities, however do not understand the reasons of this domain. It is indispensable that the teacher, in its pedagogical action, offers chances so that the pupil reflects on the executed motor action. Being thus, when facing cognitives conflicts, the citizen will find situations for (re)construir its knowledge, extending the understanding of its reality.